Trends in Physical Dating Violence Victimization Among U.S. High School Students, 1999–2011 - ROTHMAN, EMILY F. (2013)
Dating violence is a serious form of violence that places students at risk for injury, death, and negative mental health sequelae. The current analysis presents data on the prevalence of dating violence over a 12-year period among a nationally representative sample of high school-attending youth in the United States, stratified by race and gender. Data from the national Youth Risk Behavior Surveillance System (YRBSS) 1999–2011 revealed that physical dating violence victimization rates are similar for males and females; the 12-year prevalence rate of physical dating violence victimization was 9.4% for males and 9.2% for females. Black and Multiracial students were at increased risk for dating violence victimization in comparison to their White, Asian, and Hispanic counterparts. There were no changes in the reported rate of dating violence victimization over the 12-year period.